Association analysis of thromboxane A synthase 1 gene polymorphisms with aspirin intolerance in asthmatic patients. (March 2011) - Oh, Sun-Hee; Kim, Yong-Hoon; Park, Se-Min; Cho, Sung-Hwan; Park, Jong-Sook; Jang, An-Soo; Park, Sung-Woo; Uh, Soo-Taek; Lee, Youg-Mok; Kim, Mi-Kyeong; Choi, Inseon S; Cho, Sang Heon; et al.
Aim: Thromboxane A synthase (TBXAS1) converts prostaglandin H to thromboxane A, a potent constrictor of smooth respiratory muscle. Thus, functional alterations of the TBXAS1 gene may contribute to aspirin-intolerant asthma (AIA).Materials & methods: We investigated the relationship between SNPs in the TBXAS1 gene and AIA. Asthmatics (n = 470) were categorized into AIA (20% or greater decreases in forced expiratory volume in 1 s [FEV1 ], or 15% to 19% decreases in FEV1 with naso-ocular or cutaneous reactions) and aspirin-tolerant asthma (ATA). A total of 101 SNPs were genotyped. mRNA expression of the TBXAS1 gene by peripheral blood mononuclear cells and plasma thromboxane B2 (TXB2) concentrations were measured by reverse transcriptase (RT)-PCR and ELISA.Results: Logistic regression analysis showed that the rare allele frequency of rs6962291 in intron 9 was significantly lower in the AIA group (n = 115) than in the ATA group (n = 270) (p corr = 0.04). The linear regression analysis revealed a strong association of rs6962291 with the aspirin challenge-induced FEV1 fall (p = 0.003). RT-PCR revealed an exon-12-deleted splice variant. We measured TBXAS1 mRNA levels in peripheral blood mononuclear cells. The mRNA levels of the full-length wild-type and splice variant were significantly higher in the TT homozygotes than in the AA homozygotes of rs6962291 (1.00 ±± 0.18 vs 0.57 ±± 0.03 and 1.00 ±± 0.18 vs 0.21 ±± 0.05, p = 0.047 and 0.001, respectively). The plasma TXB2 level was significantly lower in rs6962291 AA carriers than in rs6962291 TT (p = 0.016) carriers.Conclusion: The rare allele of rs6962291 may play a protective role against aspirin hypersensitivity via a lower catalytic activity of the TBXAS1 gene, attributed to the increase of a nonfunctioning isoform of TBXAS1 . Original submitted 26 August 2010; Revision submitted 29 October 2010.